262. A STUDY OF METASTATIC LOCATION AND PROGNOSIS FOR ESOPHAGEAL CANCER WITH ONE OR TWO METASTATIC LYMPH NODES. (24th September 2022) - Natsuki, Seiji; Lee, Shigeru; Tanaka, Hiroaki; Mori, Takuya; Deguchi, Sota; Miki, Yuichiro; Yoshii, Mami; Tamura, Tatsuro; Toyokawa, Takahiro; Maeda, Kiyoshi
Abstract: Esophageal cancer has high frequency of lymph node (LN) metastasis and poor prognosis, and often relapse early even after radical esophagectomy. Extensive LN dissection has made it possible to grasp the detailed metastatic status and the relationship between LN metastasis and prognosis. It is necessary to study more about metastatic style and prognostic factors for minimalization of surgical invasion and individualization of treatment. We analyzed about metastatic location, prognosis and recurrence for esophageal cancer cases with a few LN metastasis. We study 168 stageII, III esophageal cancer cases that underwent radical esophageal resection with regional LN dissection (D2 or more) from January 2015 to December 2017. Those cases included 37 or 29 cases with one or two LN metastasis. The number of cases on each tumor location (Ce/Ut/Mt/Lt/Ae) were 4/19/80/55/10 cases. On LN dissection, D2 were 68 cases and D3 were 100 cases. In a comparison of survival rate, age (<65/≧65), lymphatic invasion, the number of metastatic lymph node have significant difference. The 5-years overall survival rate of esophageal cancer with one or two metastatic LNs was each 82.9% or 65%. Most of a few LN metastasis cases have first group LN metastasis (11th Japanese Classification of Esophageal Cancer), for example No.106rec or abdominal LNs, but we didn't sometimes detect them prior to surgery. Esophageal cancer with a few metastatic lymph nodes had relatively good prognosis, and metastasis was likely to stay nearby the primary lesion. However, it is difficult to detect metastasis precisely prior to surgery, so developing the further technique of diagnosis and individualized treatment are expected in the future.